2016
DOI: 10.1007/s11042-016-3995-9
|View full text |Cite
|
Sign up to set email alerts
|

Assisstive technology application for enhancing social and language skills of young children with autism

Abstract: In this paper we present an assistive system designed for supporting young children affected by autism in their process of learning pronunciation and meaning of new words. The system is built-up of a mobile application and objects identifiers which in our case were Estimote Beacon sensors. The system requires active participation of a parent who selects words to learn, records pronunciation of object names, selects illustrations, and activates and turns off the application. The entire process is designed to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Several studies showed that most people with autism show a natural affinity for technology and a good disposition for using technology and learning through the use of computers [14]. This is because the environment and context that these experiences provide are predictable and structured, which helps people with ASD to maintain their routines and repetitive behaviors without affecting their comfort [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that most people with autism show a natural affinity for technology and a good disposition for using technology and learning through the use of computers [14]. This is because the environment and context that these experiences provide are predictable and structured, which helps people with ASD to maintain their routines and repetitive behaviors without affecting their comfort [15].…”
Section: Resultsmentioning
confidence: 99%
“…Some interesting examples of new technological approaches are the use of sensors, virtual reality, virtual agents, augmented reality, geolocation, and Kinect, as presented in the following studies. Wojciechowski et al [15] developed a mobile application that, in conjunction with the use of Estimote Beacon sensors to identify objects, supports children with ASD in pronouncing new words and identifying their meanings. Lorenzo et al [16] proposed an application that uses virtual reality and robots with cameras to detect children’s emotions, adapt system interactions and thus develop social skills in students with autism spectrum disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Often, she finds no motivation to relate to others. Thus, the child may experience delays in acquiring language skills, avoiding joining a group in social situations, as they believe that it isn't necessary to communicate [Wojciechowski and Al-Musawi 2017].…”
Section: Autismmentioning
confidence: 99%
“…TEA patients can present excellent visual perception. Visual methods are often the best way to access the autistic children minds and support them in expressing themselves [Wojciechowski and Al-Musawi 2017]. In this context, several research kinds developed games for mobile devices (iPads, Tablets, among others).…”
Section: Autism and Digital Gamesmentioning
confidence: 99%
“…The paper titled BAssisstive technology application for enhancing social and language skills of young children with autism^by Wojciechowski and Al-Musawi [9], investigates how the technology can assist autistic children in learning pronunciation and meanings of new words and proposes a novel assistive system that is built-up of a mobile application and uses Estimote Beacons to identify objects. The system allows an autistic child to learn objects' names or sounds by hearing the words pronounced by a parent.…”
Section: Summary Of the Accepted Papersmentioning
confidence: 99%